FACTORS INFLUENCING MUSCLE DAMAGE FROM ISOMETRIC EXERCISE. Issue 7 (11th March 2014) - Allen, T; Jones, T; Tsay, A; Morgan, D; Proske, U
Abstract : Background: Most studies of exercise-induced muscle injury have focussed on eccentric contractions, which are known to produce damage and delayed soreness. It is less well known that isometric contractions also produce damage and soreness. This is a study of the damaging effects of isometric exercise. Objective: To investigate the contributions of factors such as muscle length, force level, duration of contraction and number of contractions to muscle damage following isometric exercise of elbow flexor muscles. Design: The study comprised 6 separate experiments using a repeated measures design. One arm acted as the experimental arm, while the other acted as the control. Damage measures were obtained pre-exercise, then at 0h, 2h and 24h post-exercise. Setting: Exercise laboratory. Participants: 50 untrained adults (29 male, 21 female) with no previous upper limb injuries. Interventions: Exercise with isometric maximum voluntary contractions (MVCs) by each arm. The control arm always performed 30 MVCs, each 4s duration at an included elbow angle of 155° (long muscle length), with 1 min rest between contractions. In 6 experiments, altered variables for the experimental arm included muscle length, number of contractions, duration of contractions and duration of relaxation. Main outcome measurements: Damage measures: MVC force, soreness rating, tenderness threshold. Exercise measures: muscle force, joint angle, contraction number, contraction duration, relaxation time, total contraction time. Results: Post-exercise force deficit and muscle soreness were significantly greater for muscles exercised at longer length, despite force being significantly lower at these lengths. A longer relaxation phase did not significantly increase force deficit or soreness. The total contraction time had a greater influence on force deficit than either the number or duration of contractions. Conclusions: Muscle damage from isometric contractions was principally related to muscle length and total contraction time, not number of contractions. Damage predominantly occurred during the plateau phase of each contraction and not the relaxation phase.